2010
DOI: 10.1590/s1415-47572010000300014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymorphisms in the Slc11a1 coding region on resistance to brucellosis by macrophages in vitro and after challenge in two Bos breeds (Blanco Orejinegro and Zebu)

Abstract: The resistance/susceptibility of selected cattle breeds to brucellosis was evaluated in an F1 population generated by crossing animals classified as resistant (R) and susceptible (S) (R x R, R x S, S x R, S x S) based on challenges in vitro and in vivo. The association between single nucleotide polymorphisms identified in the coding region of the Slc11a1 gene and resistance/susceptibility was estimated. The trait resistance or susceptibility to brucellosis, evaluated by a challenge in vitro, showed a high heri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…Differences between Zebu (B. taurus indicus) and European (B. taurus taurus) cattle in terms of natural resistance to diseases have also been reported (Martínez et al, 2010;Macêdo, 2012); however, whether these cattle differ in their peripheral blood leukocyte profiles is unclear, although this may account for the more efficient immunity observed in some breeds. Importantly, some evidence suggests that peripheral blood leukocytes from Zebu may respond differently than cells from European breeds when stimulated (Turni et al, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…Differences between Zebu (B. taurus indicus) and European (B. taurus taurus) cattle in terms of natural resistance to diseases have also been reported (Martínez et al, 2010;Macêdo, 2012); however, whether these cattle differ in their peripheral blood leukocyte profiles is unclear, although this may account for the more efficient immunity observed in some breeds. Importantly, some evidence suggests that peripheral blood leukocytes from Zebu may respond differently than cells from European breeds when stimulated (Turni et al, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…However, mortality and morbidity of this livestock species due to infection by intracellular pathogens cause significant economic losses. Resistance to disease is a particularly important attribute of livestock in low‐input production systems in the tropics and developing countries and is often the critical factor in the sustainability of such systems (Martinez et al ., ). There are programmes that exploit selective breeding for disease‐resistant/tolerant genotypes as a new approach to control intracellular infections.…”
Section: Discussionmentioning
confidence: 97%
“…Recent literatures on cattle (Martinez et al ., ; Paixao et al ., ) and buffalo (Borriello et al ., ; Crisa et al ., ) have attempted to associate with the polymorphic microsatellite located in the 3′untranslated region (3′UTR) of the gene. The 3′UTR region in Slc11a1 of cattle has no significant association with resistance to brucellosis in vivo (Paixao et al ., ), and this is in contrary in vitro (Martinez et al ., ). Meanwhile, polymorphism in 3′UTR region in Slc11a1 of buffalo is associated with resistance to brucellosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although resistance or susceptibility to disease involves multifactorial mechanisms, it has been reported that Zebu cattle tend to have a higher degree of natural resistance to diseases when compared to European cattle [ 27 - 31 ]. Analyzing the profile of peripheral blood leukocytes of different bovine breeds, we recently demonstrated that Guzerat cattle comparatively has increased levels of circulating leukocytes, especially monocytes, eosinophils, T lymphocytes (particularly CD4 + T cells) and non-B/non-T (NTNB) lymphocytes, with a decreased percentage of B lymphocytes, and consequent increase in the T/B and CD4 + /CD8 + ratio [ 29 ].…”
Section: Discussionmentioning
confidence: 99%